Legal Governance of Customary Village Enterprises for Sustainable Cultural Tourism - I Dw Made Rama Pradnyandita; I Wayan Wesna Astara; Simon Nahak (Inovasi Pratama Internasional. Ltd, 2027)
The governance of customary village enterprises has become increasingly important in promoting sustainable cultural tourism, yet limited research has examined how legal governance shapes the effectiveness of these institutions within a pluralistic legal system. This study investigates the legal governance of Baga Utsaha Padruwen Desa Adat (BUPDA) as a customary village enterprise and evaluates its contribution to sustainable cultural tourism. Employing a mixed-method legal research design, the study integrates statutory, conceptual, and socio-legal approaches through the analysis of legislation, institutional documents, interviews, and field observations. The findings demonstrate that BUPDA operates within an integrated framework of national legislation, regional regulations, customary village rules, and local governance mechanisms that collectively establish legal certainty and institutional legitimacy. Beyond serving as an economic entity, BUPDA strengthens participatory governance, preserves cultural values, and supports sustainable tourism through community-based management. Nevertheless, institutional effectiveness remains constrained by limited human resource capacity, governance quality, and regulatory harmonization. The principal novelty of this study lies in developing a legal governance perspective that positions customary village enterprises as institutional instruments linking legal pluralism, indigenous economic governance, and sustainable cultural tourism. The study concludes that strengthening legal coordination, institutional capacity, and adaptive governance is essential for improving the long-term sustainability of customary village enterprises. Future research should comparatively examine customary economic institutions across different indigenous communities to develop broader governance models applicable to sustainable tourism policies.